Halogenated building blocks for 2D crystal engineering on solid surfaces: lessons from hydrogen bonding. Issue 13 (6th March 2019) - Mukherjee, Arijit; Sanz-Matias, Ana; Velpula, Gangamallaiah; Waghray, Deepali; Ivasenko, Oleksandr; Bilbao, Nerea; Harvey, Jeremy N.; Mali, Kunal S.; De Feyter, Steven
Abstract : We test whether the similarities between halogen and hydrogen bonds could be used to design a surface-confined halogen-bond based network. Abstract : Halogen bonding has emerged as a promising tool in two-dimensional (2D) crystal engineering. Since halogen bonds are similar to hydrogen bonds in a number of aspects, the existing knowledge of hydrogen bonded systems can be applied to halogenated systems. Here we evaluate the applicability of a retrosynthetic approach based on topological similarity between hydrogen and halogen bonds to obtain predictable halogen bonded networks. The self-assembly of 1, 3-dibromo-5-alkoxybenzene derivatives was studied in analogy with well-explored alkoxy isophthalic acids using a combination of experimental and theoretical tools. Scanning tunneling microscopy (STM) characterization of the networks formed at the liquid–graphite interface revealed that while the retrosynthetic approach works at the level of small clusters of molecules within the 2D network, the overall structure of the network deviates from the anticipated structure. The monolayers consist of fractured rows of halogen-bonded modules instead of the expected continuous lamellar structure. Each module consists of a discrete number of halogen-bonded molecules. The interactions responsible for the stabilization of halogen bonded dimers are delineated through detailed density functional theory (DFT) calculations coupled with natural bonding orbitals (NBO) and perturbation analysis. A modified force field that includes an extra charged site to imitate the σ hole on the halogen atom was developed and applied to extract total potential energies of the anticipated and observed networks. Plausible reasons for the deviation from the anticipated structure are discussed. Finally, a modified molecular design that allows successful application of the hydrogen bond–halogen bond analogy was tested experimentally.